Application of lanthanide luminescence in probing enzyme activity. Issue 50 (23rd May 2018) - Hewitt, Sarah H.; Butler, Stephen J.
Abstract : Assays to monitor enzyme reactions are vital for studying enzyme mechanism, function and inhibition. We focus on recent progress in the development of enzyme activity assays using lanthanide(iii ) luminescence, covering Ln(iii )-labelled biomolecules, Ln(iii ) ion encapsulation within peptide sequences, reactivity-based Ln(iii ) probes and discrete Ln(iii ) complexes. Abstract : Enzymes play critical roles in the regulation of cellular function and are implicated in numerous disease conditions. Reliable and practicable assays are required to study enzyme activity, to facilitate the discovery of inhibitors and activators of enzymes related to disease. In recent years, a variety of enzyme assays have been devised that utilise luminescent lanthanide(iii ) complexes, taking advantage of their high detection sensitivities, long luminescence lifetimes, and line-like emission spectra that permit ratiometric and time-resolved analyses. In this Feature article, we focus on recent progress in the development of enzyme activity assays based on lanthanide(iii ) luminescence, covering a variety of strategies including Ln(iii )-labelled antibodies and proteins, Ln(iii ) ion encapsulation within defined peptide sequences, reactivity-based Ln(iii ) probes, and discrete Ln(iii ) complexes. Emerging approaches for monitoring enzyme activity are discussed, including the use of anion responsive lanthanide(iii ) complexes, capable of molecular recognition and luminescence signalling of polyphosphate anions.